An examination of an e-authentication service as an intervention in e-mail risk perception. Issue 1 (2nd January 2017) - Chen, Rui; Wang, Jingguo; Herath, Tejaswini; Rao, H. R.
ABSTRACT: In this article, we develop a three-stage study to examine the role of an e-mail authentication and identification service (eATS) intervention in affecting end-user e-mail risk perceptions. We deploy the eATS and find that it reduces users' risk perception. Pre-intervention risk perception is found to be positively associated with user perception of the e-authentication service's usefulness. Moreover, perceived usefulness of the service negatively relates to e-mail risk perception in the post-use stage. Finally, privacy concerns related to the e-authentication service dilute this relationship between usefulness of service and e-mail risk perception reduction.